KRISIS DAN REFORMASI: EKSPROPRIASI DALAM PERJANJIAN INVESTASI BILATERAL DI NEGARA DUNIA KETIGA - Syahrul Fauzul Kabir (Faculty of Law, Parahyangan Catholic University, 2023)
Since its inception, expropriation has always been controversial. In the present time, amidst the crisis and reform of bilateral investment treaties (BIT), expropriation has become increasingly complex in theory and practice. Theoretically, for instance, there is no clear boundary between expropriation that requires compensation, and the right to regulate similar to expropriation but does not require compensation. This situation becomes more complicated due to the problem of inconsistency and incoherence of arbitral awards. Therefore, it is important to understand how the concept of expropriation is understood by experts and interpreted by the arbitration tribunal; while also comparing how the global south use that concept within their BITs (in this case, India, Brazil, South Africa) to find best-practices. The method used in this research is juridical-normative and comparative. Amidst the BIT’s crisis particularly regarding expropriation, the global south has made various attempts to reform its BIT model. Exceptions forexpropriation are included within the right to regulate. Expropriation and the right to regulate indeed have similar legal requirements (i.e.: pursuance of a public interest, non-discriminatory manner, due process of law) yet different legal effect regardingthe payment of compensation as another condition for expropriation vis-à-vis the absence of compensation inthe right to regulate. In general, taking into account the respective adjustments, the global south is relatively balancing the investment interest vis-a-vis public interest by modernizing the concept of expropriation in their BITs.